Study on evaluation of rail axial stress with ultrasonic wave method (Application of wavelet transform results) - Keisuke OOSUMI; Masanori TAKUMA; Kenichi SAITOH; Yoshimasa TAKAHASHI; Tomohiro SATO; Ken YAMAMOTO (Nihon Kikai Gakkai ronbunshu, 2019)
The part of rail joint becomes the cause of the disadvantage points such as ride discomfort, undesired sound and track maintenance, etc. For restraining those points, the long rail made by welding the standard length rails has been developed. However, the problems of the buckling caused by the axial stress (i.e. the thermal stress which is brought out by the weather conditions or the friction heat between wheel and rail) of the rail have been pointed out. Therefore, some evaluation techniques for buckling management have been proposed. In this study, the relationship between the increase in compressive stress and the behaviors of the characteristics of the wavelet transform (i.e. a kind of time-frequency analysis) results of ultrasonic echoes was researched. The stress was increased in 10 [MPa] interval, and the echo at each stress was detected. From the results of experiment and analysis, it became clear that there is the relatively correlation between three characteristics and the stress. They are RMWC, RWE and RKTW respectively. The value of each RMWC, RWE and RKTW shows the ratio to the initial value (i.e. shows at 0[MPa] in this case) of MWC (i.e. the maximum wavelet coefficient), WE (i.e. wavelet energy) and KTW (i.e. the kurtosis of the time fluctuation waveform of the wavelet coefficient of the frequency that indicates MWC). Therefore, it was able to show the possibility of comparatively accurately predicting the increment of the stress by comparing the transitions of those.